Associations of current and remitted major depressive disorder with brain atrophy: the AGES-Reykjavik Study - Geerlings, Mirjam I. (Psychol Med, 2012)
BACKGROUND: To examine whether lifetime DSM-IV diagnosis of major depressive disorder (MDD), including age at onset and number of episodes, is associated with brain atrophy in older persons without dementia. METHODS: Within the population-based AGES-Reykjavik Study 4,354 persons (mean age 76±5 years, 58% women) without dementia had a 1.5Tesla brain MRI. Automated brain segmentation total and regional brain volumes were calculated. History of MDD, including age at onset and number of episodes, and MDD in the past 2 weeks was diagnosed according to DSM-IV criteria using the MINI International Neuropsychiatric Interview. RESULTS: Of the total sample, 4.5% reported a lifetime history of MDD; 1.5% had a current diagnosis of MDD (including 75% with a prior history of depression) and 3.0% had a past but no current diagnosis (remission). After adjusting for multiple covariates, compared to participants never depressed, those with current MDD (irrespective of past) had more global brain atrophy (B=−1.25%; 95%CI −2.05 to −0.44%), including more gray and white matter atrophy in most lobes as well as more atrophy of the hippocampus and thalamus. Participants with current, first onset, MDD also had more brain atrophy (B=−1.62%; 95%CI −3.30 to 0.05%), while those remitted did not (B=0.06%; 95%CI −0.54 to 0.66%). CONCLUSION: In older persons without dementia, current MDD, irrespective of prior history, but not remitted MDD, was associated with widespread gray and white matter brain atrophy. Prospective studies should examine whether MDD is a consequence of or contributes to brain volume loss and development of dementia.